Red flags for financial fraud: uncovering the wirecard fraud case - Teixeira, Sara Filipa David (2022)
Wirecard AG, a forward-thinking corporation that aimed to reshape the payment industry, declared bankruptcy in June 2020. The company reported missing a total of EUR 1.9 billion, assuming they had probably never existed. This incident harmed the credibility of the German’s financial regulator and the reputation of the external auditors. Wirecard’s Annual Reports and other sources, such as the Financial Times newspaper, were examined in light of the thirty-seven red flags identified in Murcia and Borba’s (2007) study, which was supported on the International Standard Auditing (ISA) 240, to determine whether the red flags included in this standard were sufficient to indicate potential Financial Statement fraud in the Wirecard case. Twenty-four of the thirty-seven red flags examined sign potential fraud. Nineteen of these red flags are included in ISA 240, leading to the conclusion that the red flags present in that standard were sufficient to indicate potential Financial Statement fraud in the Wirecard case, and any outsider analyst could have detected and incorporated these early warning alarms into their decision-making. This also makes clear that auditors neglected the red flags signalization in the Wirecard case. Although ISA 240 proved to be effective, five of the twenty-four red flags were absent in this standard. These red flags are significant since they expose business issues, implying that a modification of ISA 240 to integrate similar essential red flags is required to make this standard more effective. Moreover, the Wirecard case raised six new significant red flags that can be incorporated in ISA 240.